Defining the Scope of a Factory Under the Factory Act - Chitcham, Sophonpisut; Lengvittaya, Jaral; Suparp, Utid (Ph.D. in Social Sciences Journal, 2025)
This academic article aims to analyze the problem of defining the scope of a factory under the Factory Act by using the concept of controlling the operation of industrial factories, the scope of being a factory under the Factory Act of the Kingdom of Thailand, the Commonwealth of Australia, New Zealand, and the Republic of Iceland as a framework for analysis in order to find the appropriateness of defining the scope of being a factory. Findings are as follows: The amendment of the Factory Act (No. 2) B.E. 2562 to amend the definition of the scope of being a “factory” under Section 5 of the Factory Act B.E. 2535 from a business with a machine power of 5 horsepower or 7 workers or more to a machine power of 50 horsepower or 50 workers or more has resulted in a gap in the size of the horsepower of the machine by 10 times and causing factories using machines with a size of 5 horsepower but not exceeding 50 horsepower to not fall under the definition of being a factory that must be under the supervision of the Factory Act. It also allows the increase in the number of small industrial factories that do not fall under the definition of a factory in this Act to be able to open a business nationwide, be located in any building or location, and do not have to apply for a factory construction permit. Therefore, the scope of being a new factory should be amended. It is stipulated that buildings, places or vehicles that use machinery with a total power of 20 horsepower or equivalent to 20 horsepower or more, or that employ 20 or more workers, whether or not using machinery, are to operate a factory, in accordance with the type or kind of factory specified in the Ministerial Regulations.